STRATEGI MANAJEMEN LANSKAP WISATA TAMAN NOSTALGIA KOTA KUPANG, NUSA TENGGARA TIMUR (Jurnal Ilmiah Pariwisata, 2014)
Research landscape management strategy Nostalgia Parks Kupang, aims to analyze the landscape character nostalgic tour of the gardens, the potential and constraints, as well as to propose management strategies garden tour of the city. The research method using three analyzes, namely SWOT analysis to identify strengths, weaknesses, opportunities and threats in the region; analysis of the carrying capacity of the region, and analysis of the characteristics, perceptions, and preferences of visitors. The study was conducted in September 2014 to January 2015. The results showed that the preparation of several important strategies park management system, especially in the area of economic value utilization system, enforcement of visitors travel to / tenant clearly, design improvements (re-design) and garden materials that facilitate / gives a sense of comfort for users, promoting the implementation of local arts and cultural activities that interested visitors, as well as maintaining a special green open space for wildlife.
Keywords: Management, Travel Landscape, City Park